1999
DOI: 10.1177/104063879901100105
|View full text |Cite
|
Sign up to set email alerts
|

Differential Serologic Response to Mycoplasma Ovipneumoniae and Mycoplasma Arginini in Lambs Affected with Chronic Respiratory Disease

Abstract: Abstract. An enzyme-linked immunoabsorbent assay (ELISA) was used to evaluate the levels of antibodies to Mycoplasma ovipneumoniae and M. arginini in lambs with chronic respiratory disease. Sera were obtained from lambs in several flocks at various stages of the clinical disease and tested with sodium dodecyl sulfate (SDS)-treated M. ovipneumoniae and M. arginini whole cells and a crude capsular extract of M. ovipneumoniae as the antigens. There were low levels of antibody to M. ovipneumoniae in flocks sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…Regarding the serological responses of ewes following inoculation with various strains of M. agalactiae, high levels of antibodies have been previously reported to be closely associated with induction of clinical signs and high levels of infection, as in other Mycoplasma infections such as M. ovipneumoniae in adult sheep [13] or M. agalactiae in lambs [19]. In the present study, in spite of comparable levels of infection, great individual variations were observed and some ewes remained seronegative while others developed very high titres; thus the highest titres (>1000 units) were obtained with the supposed "asymptomatic" strain 9523, while 2 ewes remained negative with the reference virulent strain P89.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the serological responses of ewes following inoculation with various strains of M. agalactiae, high levels of antibodies have been previously reported to be closely associated with induction of clinical signs and high levels of infection, as in other Mycoplasma infections such as M. ovipneumoniae in adult sheep [13] or M. agalactiae in lambs [19]. In the present study, in spite of comparable levels of infection, great individual variations were observed and some ewes remained seronegative while others developed very high titres; thus the highest titres (>1000 units) were obtained with the supposed "asymptomatic" strain 9523, while 2 ewes remained negative with the reference virulent strain P89.…”
Section: Discussionmentioning
confidence: 99%
“…or through movement associated with trade (2). The asymptomatic presence of M. ovipneumoniae could also predispose goats to pneumonia caused by other organisms, as was previously observed in sheep (16). The lack of positive samples from adult goats could be explained by the capacity of some adult goats to clear the infection or at least inhibit bacterial growth (17).…”
mentioning
confidence: 76%
“…In vitro studies have shown that M. ovipneumoniae specific antibodies can have protective functions by mediating opsonization and phagocytosis of the Mycoplasma [35]. Likewise, Niang et al [36] found increased levels of M. ovipneumoniae-reactive antibodies in lambs that had recovered from the clinical M. ovipneumoniae infection. In our study, lambs had no detectable M. ovipneumoniae specific antibodies prior to experimental inoculation but developed a significant, stable antibody response within two weeks after infection, confirming previous studies that have tracked humoral responses to M. ovipneumoniae [37].…”
Section: Discussionmentioning
confidence: 99%